Effect of terbium(III) chloride on the micellization properties of sodium decyl- and dodecyl-sulfate solutions - Neves, A. C. S. (2007)
The effect of TbCl3 on the aggregation processes of the anionic surfactants sodium decyl sulfate (SDeS) and sodium dodecyl sulfate (SDS) has been investigated. Electrical conductivity data, combined with Tb(III) luminescence measurements suggest that the formation of micelles involving TbCl3 and SDS occurs at concentrations below the critical micelle concentration (cmc) of the pure surfactants; the formation of these mixed aggregates was also monitored by light scattering, which indicates that the addition of TbCl3 to surfactant concentration at values below the pure surfactant cmc results in a much greater light scattering than that found with pure sodium alkylsulfate surfactant micelles. This phenomenon is dependent upon the alkyl chain length of the surfactant. With Tb(III)/DS-, complexes are formed with a cation/anion binding ratio varying from 3 to 6, which depends upon the initial concentration of Tb(III). This suggests that the majority of the cation hydration water molecules can be exchanged by the anionic surfactant. When the carbon chain length decreases, interactions between surfactant and Tb(III) also decrease, alterations in conductivity and fluorescence data are not so significant and, consequently, no binding ratio can be detected even if existing. The surfactant micellization is dependent on the presence of electrolyte in solution with apparent cmc being lower than the corresponding cmc value of pure SDS.